Canadian and UK/Ireland practice patterns in lumbar puncture performance in febrile neonates with bronchiolitis. Issue 3 (6th February 2019) - Simone, Laura; Lyttle, Mark D; Roland, Damian; Stephens, Derek; Schuh, Suzanne
Abstract : Background: Serious bacterial infections in young infants with bronchiolitis are rare. Febrile infants <1 month old with bronchiolitis often receive a lumbar puncture (LP), despite limited data for this practice and lack of clinical practice guidelines for this population. The primary objective was to investigate practice patterns in performance of LPs in the ED management of febrile infants aged ≤30 days with bronchiolitis. Methods: A cross-sectional survey of two national paediatric emergency research networks (PediatricEmergency Research Canada (PERC) and the PediatricEmergency Research UK/Ireland (PERUKI)) was conducted January to November 2017 using a modified Dillman technique. The survey was preceded by a clinical vignette describing a well appearing, 21-day-old infant with low-grade fever, respiratory findings typical of bronchiolitis and no perinatal serious bacterial infection (SBI) risk features. Results: The response rate from PERC was 169/250 (68%) and 172/201 (86%) from PERUKI. Nine physicians in training were excluded, leaving 332 eligible participants. Although most physicians believe that neonates with bronchiolitis rarely have meningitis (PERC 141/161 (87.6%); PERUKI 154/171 (90%)) and feel comfortable diagnosing bronchiolitis in this group (PERC 136/161 (84.5%); PERUKI 143/171 (83.6%)), there was significant variation in the proportion who would be likely/very likely to perform an LP (PERC 100/161 (62.1%); PERUKI 15/171 (8.8%)) (p<0.0001). Practice in Canada, <10 years in practice and lack of comfort with diagnosing bronchiolitis represent multivariable predictors of LP; OR 23.7 (95% CI 11.7 to 47.9), 2.3 (95% CI 1.2 to 4.2) and 2.5 (95% CI 1.1 to 5.0), respectively. Rapid knowledge of respiratory syncytial virus positivity would decrease LP probability from 35.4% to 20.2%. Conclusion: Estimated probability of performing LPs and other interventions in otherwise healthy febrile neonates with bronchiolitis is highly variable between emergency physicians in Canada and the UK/Ireland. Network, <10 years in ED practice and comfort level with diagnosing bronchiolitis in newborns constitute independent predictors of the likelihood of LP performance.